Basic Mold Prevention - Hyun-Jeong Lee; Virginia Peart (EDIS)
FCS3255, a 2-page fact sheet by Hyun-Jeong Lee and Virginia Peart, will help homeowners understand why and when mold and mildew start to grow in our homes and basic ways to prevent this from occurring. This publication combines, updates, and supersedes FCS3042, FCS5232-11, and FCS3245. Published by the UF Department of Family, Youth and Community Sciences, January 2007.